2017
DOI: 10.1007/s11414-017-9581-8
|View full text |Cite
|
Sign up to set email alerts
|

Inter-Agency Strategies Used by State Mental Health Agencies to Assist with Federal Behavioral Health Parity Implementation

Abstract: State mental health agencies have potential to enhance implementation of the Mental Health Parity and Addiction Equity Act (MHPAEA), particularly through collaborations with state insurance agencies. Little research, however, has examined state agencies’ MHPAEA implementation strategies. The study purpose was to describe the trend in collaboration between state mental health agencies and other state agencies to assist with MHPAEA implementation between 2010–2015 and characterize implementation strategies used.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…This research builds on prior work demonstrating the generalizability of ERIC strategies in health policy implementation research [9,23]. Purtle et al categorized ERIC strategy use by state mental health agencies to promote federal behavioral health parity implementation [9]. Like Purtle et al, we found that providing interactive assistance was a frequently used policy implementation strategy during the Implementation phase.…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations
“…This research builds on prior work demonstrating the generalizability of ERIC strategies in health policy implementation research [9,23]. Purtle et al categorized ERIC strategy use by state mental health agencies to promote federal behavioral health parity implementation [9]. Like Purtle et al, we found that providing interactive assistance was a frequently used policy implementation strategy during the Implementation phase.…”
Section: Discussionsupporting
confidence: 58%
“…Research is needed to explore the utility of each strategy, or bundled strategies, for promoting adoption of evidence-based substance use treatment services. Our study and others [9,23] suggest directions for future health policy implementation science including further identification and specification of strategies for promoting policy adoption, and quantitative measurements of the utility of health policy implementation strategies in global settings.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…A range of empirical studies as well as observations from veteran researchers and policy-makers point to low and declining rates of state and federal funding for both support to and research on implementation support for effective behavioral health practices. [33][34][35] As such, it is critical that established providers of TA such as NTTAC have guidance to efficiently and effectively achieve their mission. Unfortunately, the literature focused on how best to provide evidence-based TA is even more limited than that focused on specific evidence-based behavioral health treatments.…”
Section: Implications For Behavioral Healthmentioning
confidence: 99%